Keep out of reach of children : Reye's syndrome, aspirin, and the politics of public health - Largent, Mark A. (Bellevue Literary Press pathography., 2015)
"A modern medical mystery about an illness that ravaged healthy children, changed policy, and vanished before a cause was found"--Provided by publisher.